How can health literacy and client recall/memory of clinical information be maximised in the field of Speech-Language Pathology? : an exploratory study of clients and therapists in the Western Cape - Von Wuhlisch, Friderike Schmidt (Division of Communication Sciences and Disorders, 2014)
Includes abstract.